Sex-specific interaction effects of age, occupational status, and workplace stress on psychiatric symptoms and allostatic load among healthy Montreal workers. (November 2013) - Juster, Robert-Paul; Moskowitz, D. S.; Lavoie, Joel; D'Antono, Bianca
Abstract Socio-demographics and workplace stress may affect men and women differently. The aim of this cross-sectional study was to assess sex-specific interactions among age, occupational status, and workplace Demand-Control-Support (D-C-S) factors in relation to psychiatric symptoms and allostatic load levels representing multi-systemic "wear and tear". It was hypothesized that beyond main effects, D-C-S factors would be moderated by occupational status and age in sex-specific directions predictive of subjective psychiatric symptoms and objective physiological dysregulations. Participants included healthy male (n = 81) and female (n = 118) Montreal workers aged 20 to 64 years (Men: M = 39.4 years, SD = 11.3; Women: M = 42.8 years, SD = 11.38). The Job Content Questionnaire was administered to assess workplace D-C-S factors that included psychological demands, decisional latitude, and social support. Occupational status was coded using the Nam–Powers–Boyd system derived from the Canadian census. Psychiatric symptoms were assessed using the Beck Anxiety Scale and the Beck Depression Inventory II. Sex-specific allostatic load indices were calculated based on fifteen biomarkers. Regression analyses revealed that higher social support was associated with less depressive symptoms in middle aged (p = 0.033) and older men (p = 0.027). Higher occupational status was associated with higher allostatic load levels for men (p = 0.035), while the reverse occurred for women (p = 0.048). Women with lower occupational status but with higher decision latitude had lower allostatic load levels, as did middle-aged (p = 0.031) and older women (p = 0.003) with higher psychological demands. In summary, age and occupational status moderated workplace stress in sex-specific ways that have occupational health implications.